Reception of the Christianity ideas in the literature of the early Middle Ages (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The article deals with common tendencies of the early Middle Ages clerical lit-erature development. Special attention is paid to genre-thematic variety of didactic and liturgical works and also a hagiography as well.
Keywords: the clerical literature; an ascesis; a hagiography, di-dactic products